(untitled) (GYMNASIUM, 2017)
It is well known that health is one of the important components of quality of life. The research objective was to select and structure the specific means, physical therapy and swimming to help improve recovery, to increase quality of life and socio-professional reintegration of these young people. After applying physical therapist treatment resulted in decreases in pain intensity, and improve mobility of the spine up to around normal. The essential factor that can ensure a successful therapeutic medium and long term, adaptation consists of rigorous physical therapy programs and therapeutic swimming ethiopatogenic generating elements grief. From the results of the experiment, point out the following conclusions: Structuring a program of recovery through physiotherapy and swimming, well dosed and individualized and apply it with perseverance and continuity, cause pain relief, improved joint mobility, increase muscle strength and allow for a proper social and professional activities.